Teaching Poetry Enhances Speaking Skills â€“ an Analysis Based on Select Poems - Deepa, P.; Ilankumaran, M. (International Journal of Engineering and Technology, 2018)
English has become the medium of all relevant social interactions, discussions in all circumstances globally because of its numerous functions and preferences over several other languages. Language is the primary source of communication. It helps to exchange ideas and thoughts. The language skills, though not in proper way, are acquired at school level through the constituents of English Literature such as poetry, grammar and prose. This paper focuses how teaching poetry enhances the language skills of the students. Reading literature is an interesting area and it is the mirror of society. Poetry is one of the interesting areas in Literature which always awakens the senses and promotes literary things. It serves not only a model of literature but also a model for teaching skills of language such as reading and writing. Poetry is an effective way of language teaching. It helps the people to understand culture and to know the language. It also gives pleasure to the readers and gives them new models in their life to follow. Learning literature provides a platform to improve the communication skills of students. When the students read poetry, it improves their vocabulary, sentence formation, syntax, fluency and the creative skills. The genre poetry not only improves the communication skills but also improves the four skills such as LSRW ie, Listening, Speaking, Reading and writing.Â Â